2020
DOI: 10.1038/s41598-019-57006-5
|View full text |Cite
|
Sign up to set email alerts
|

Carotenoids are used as regulators for membrane fluidity by Staphylococcus xylosus

Abstract: carotenoids are associated with several important biological functions as antenna pigments in photosynthesis or protectives against oxidative stress. Occasionally they were also discussed as part of the cold adaptation mechanism of bacteria. For two Staphylococcus xylosus strains we demonstrated an increased content of staphyloxanthin and other carotenoids after growth at 10 °C but no detectable carotenoids after grow at 30 °C. By in vivo measurements of generalized polarization and anisotropy with two differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
64
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 88 publications
(69 citation statements)
references
References 61 publications
5
64
0
Order By: Relevance
“…The colonization of food with pigmented micro-organisms represents a well-known source of food spoilage documented by famous historical reports describing the discovery of Serratia marcescens and Halobacterium salinarum as spoiling organisms of polenta and codfish [1,2]. Some of these pigmented and food-related micro-organisms show a more intense pigmentation under low temperature conditions, which impairs the properties of food products under low temperature storage conditions [3]. In the course of analyses of pigmented bacterial strains from cold stored food samples, we found a pink-pigmented bacterial strain which shows a temperature-dependent intensity of pigmentation.…”
Section: Introductionmentioning
confidence: 99%
“…The colonization of food with pigmented micro-organisms represents a well-known source of food spoilage documented by famous historical reports describing the discovery of Serratia marcescens and Halobacterium salinarum as spoiling organisms of polenta and codfish [1,2]. Some of these pigmented and food-related micro-organisms show a more intense pigmentation under low temperature conditions, which impairs the properties of food products under low temperature storage conditions [3]. In the course of analyses of pigmented bacterial strains from cold stored food samples, we found a pink-pigmented bacterial strain which shows a temperature-dependent intensity of pigmentation.…”
Section: Introductionmentioning
confidence: 99%
“…ROS sensitivity of CC4533 can be tested in the presence and absence of the inhibitor of PDS. Carotenoids are used as regulators for membrane fluidity by Staphylococcus xylosus 79 . For two Staphylococcus xylosus strains there was an increase in staphyloxanthin and other carotenoids when grown at 10°C but no carotenoids could be detected when grown at 30°C 79 .…”
Section: Discussionmentioning
confidence: 99%
“…Carotenoids are used as regulators for membrane fluidity by Staphylococcus xylosus 79 . For two Staphylococcus xylosus strains there was an increase in staphyloxanthin and other carotenoids when grown at 10°C but no carotenoids could be detected when grown at 30°C 79 . CC4533 cannot grow at 37°C and appears lot less yellow-pigmented at 30°C compared to when it is grown at 22°C ( Figure 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…36 . Moreover, it has been shown that carotenoid production is increased at cold temperatures 15,16 . Carotenoids localize to the membrane bilayer and have a plethora of diverse structures which affect and localize in the membrane differently 37,38 .…”
Section: Discussionmentioning
confidence: 99%
“…Whereas, carotenoids (ß-carotene and zeaxanthin) 5 have been shown using molecular dynamics (MD) simulations to have a condensing effect similar to that of cholesterol on phospholipids 8 . Physiologically, there is evidence that hopanoids are important for growth at higher temperatures [9][10][11][12][13] , whereas carotenoids have been linked to cold acclimation in some bacteria [14][15][16] . These contrasting phenotypes for temperature acclimation suggest that hopanoids and carotenoids may serve complementary roles in modulating membrane properties.…”
Section: Introductionmentioning
confidence: 99%